The Effects of Air Pollution on COVID-19 Infection and Mortality—A Review on Recent Evidence - Ali, Nurshad; Islam, Farjana (Frontiers in Public Health, 2020)
The outbreak of COVID-19 has created a serious public health concern worldwide. Although, most of the regions around the globe have been affected by COVID-19 infections; some regions are more badly affected in terms of infections and fatality rates than others. The exact reasons for such variations are not clear yet. This short review discussed the possible effects of air pollution on COVID-19 infections and mortality based on some recent evidence. The findings of most studies reviewed here demonstrate that both short-term and long-term exposure to air pollution especially PM2.5 and nitrogen dioxide (NO2) may contribute significantly to higher rates of COVID-19 infections and mortalities with a lesser extent also PM10. A significant correlation has been found between air pollution and COVID-19 infections and mortality in some countries in the world. The available data also indicate that exposure to air pollution may influence COVID-19 transmission. Moreover, exposure to air pollution may increase vulnerability and have harmful effects on the prognosis of patients affected by COVID-19 infections. Further research should be conducted considering some potential confounders such as age and pre-existing medical conditions along with exposure to NO2, PM2.5 and other air pollutants to confirm their detrimental effects on mortalities from COVID-19.